Research and Research Education in Music Performance and Pedagogy
XVII, 202 p. 11 illus., 7 illus. in color.
Keywords: This volume is an innovative collection that transcends national boundaries and provides new knowledge about approaches to research and research education in music. The collection brings together leading thinkers and practitioners in music research from Europe, Asia, North America and Australia. The book is designed to serve as a resource for university music departments and conservatoires, and offers insights into the development of research programs in this context.